Oxidized impurity in transition metal nitride for improving the hydrogen evolution efficiency of transition metal nitride-based catalyst. (March 2020) - Qi, Weiliang; Zhou, Ying; Liu, Siqi; Liu, Honghong; Hui, Lok Shu; Turak, Ayse; Wang, Jun; Yang, Minghui
Graphical abstract: Novel Z-scheme NiO-Ni3 N/g-C3 N4 heterostructures with reductive defects have been in-situ fabricated for efficient photocatalytic water splitting hydrogen evolution. Highlights: The metal oxdie-metal nitride heterojunction has been in-situ created by calcinations process. The metal oxdie-metal nitride-based catalyst exhibits improved hydrogen evolution performance as compared to metal nitride-based catalyst by forming Z-scheme pathway. Reductive defects on the surface of semiconductors created by ammonia treatment can boost the hydrogen evolution efficiency. Abstract: Transition metal nitrides (TMNs)-based catalyst as promising alternative for precious metal-based catalyst in hydrogen evolution have gained ever increasing research attention. However, the metastable nature of TMNs often results in the inevitable formation of metallic, oxidized and hydroxide impurities during fabrication. The effects of the inevitable impurities over TMNs in hydrogen evolution reaction are still unclear. Herein, choosing Ni3 N as a typical example, the effect of oxidized impurity in transition metal nitride for hydrogen evolution has been systematically investigated. The metal oxdie-metal nitride heterojunction which has been in-situ created by calcinations process exhibits obviously improved performance in boosting hydrogen evolution efficiency of semiconductors as compared to metal nitride by forming Z-scheme pathway. Besides, X-ray photoelectron spectroscopy (XPS) and electron paramagnetic resonance (EPR) measurements demonstrate the formation of reductive defects on the surface of semiconductors created by ammonia treatment which also boost the hydrogen evolution efficiency. Therefore, the optimal ternary sample exhibits the highest hydrogen evolution rate (151.5 μmol g −1  h −1 ) under solar light irradiation, which is about 54 times higher than that of pure sample.